2006
DOI: 10.1016/j.amjhyper.2005.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Morphofunctional Characteristics of the Left Ventricle in Clinically Hypertensive Nondiabetic Subjects

Abstract: Nondiabetic patients with metabolic syndrome showed more pronounced alterations of LV geometry and function compared with subjects without metabolic syndrome. These greater preclinical myocardial abnormalities were not accounted for by difference in age, gender, or 24-h BP and can be reasonably ascribed to the interplay of the metabolic syndrome components, making the metabolic syndrome in itself a relevant clinical problem, possibly a cardiovascular disease equivalent, that deserves aggressive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 29 publications
5
42
1
1
Order By: Relevance
“…Recently, population-based studies report that MS patients also present mild but significant left ventricular (LV) diastolic dysfunction (2,3). Cardiac fibrosis, a major cause of diastolic dysfunction, is prevalent in these MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, population-based studies report that MS patients also present mild but significant left ventricular (LV) diastolic dysfunction (2,3). Cardiac fibrosis, a major cause of diastolic dysfunction, is prevalent in these MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the RAAS and associated oxidative stress can result in mitochondrial abnormalities, altered bioenergetics and the accumulation of lipids in the heart, and thereby increase susceptibility to metabolic cardiomyopathy. 4 Although left ventricular (LV) remodeling and dysfunction have been observed in individuals with MetS, 5,6 the extent of cardiac injury in such individuals has remained unclear. A diet with a moderate fat content was found to induce metabolic abnormalities but did not result in LV diastolic dysfunction in obesity-prone Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that MetS is associated with elevated LVM, 6,7,12,[16][17][18][19][20][21][22][23][24][25] but the potential influence of gender on MetS-related LVH is controversial. 6,17,24,25 In a study conducted on 618 hypertensive patients a remarkable sex difference in the association between MetS and LVH was found; indeed, in that study, MetS was a strong determinant of LVM in women beyond the influence of body size and haemodynamic variables, whereas the relation was weaker and fully explained by the effect of confounding factors in men.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Subjects with left ventricular mass (LVM) in the upper normal range already have increased risk for CV events. 15 MetS has been associated with an increased LVM in recent reports conducted in hypertensive patients and in general population, 6,7,12,[16][17][18][19][20][21][22][23][24][25] independently of various confounding factors, such as BP values and age. However, only in a few of these studies the impact of MetS on LVM was separately analysed by gender, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%